Penurunan Kadar TOC Dan Suspended Solid Pada Air Limbah Industri Kertas Dengan Proses Koagulasi Dan Flotasi - Siti Agustina; Emmy Ratnawati (Jurnal Kimia dan Kemasan, 1998)
The Waste Water of paper industries normally contains suspended solid particles which have specific gravity lower than specific gravity of water, therefore in the waste water treatment needs flotation treatment to remove the suspended solid Research on treatment of waste water of paper industry (pH= 7.35, TOC = 331,7 mg/land SS= 796 mgll) has been done by using coagulation followed by flotation.The Waste Water of paper industry is treated by using Fe Cl3, 6H20 and Al2(S04)J 18H20 as a coagulant, NaOH as neutralizing agent, and three kinds of polymer (cationic, non ionic and anionic) as a flocculant . The optimum dosage for the best result is Al2(S04)J l8H20 300 mg/I, NaOH 100 mg/l, and anionic polymer A-2022 5 mg/l. The final result is decreasing of TOC value from 331, 7 mg/l to 38,4 mg/l and SS from 796 mg/l to 5 mg